Study of the immature stages of two species of the biting midge genus Culicoides (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2013)
Pupa of Culicoides insignis Lutz, 1913, and larva and pupa of Culicoides bambusicola Lutz, 1913 are fully described. They are illustrated and photographed using binocular microscope, phase-contrast stereoscope at oil immersion and scanning electronic microscopy, from material collected in Corrientes and Misiones provinces, Argentina. Palatum, maxilla and hypopharynx of the fourth instar larva of C. bambusicola as well as the cephalothoracic sensilla and sensillar pattern of the fi rst and fourth abdominal segment of the pupa are described for both species. The immatures of C. bambusicola are compared with Culicoides debilipalpis Lutz, 1913. Pupa of C. insignis is compared with the following related congeners: C. maruim Lutz, 1913, C. charruus Spinelli & Martinez, 1992, and C. annetae Spinelli & Borkent, 2004.